PENGGUNAAN KALSIUM HIDROKSIDA (Ca(OH)2) DAN ALUMINIUM SULFAT ((Al2SO4)3) DALAM PENGOLAHAN AIR LIMBAH SETTLING POND PADA PT. INTERNASIONAL PRIMA COAL - Kusnanto, Fransiska Angelina; Devy, Shalaho Dina; Winarno, Agus; Hasan, Harjuni; Respati, Lucia Litha (JOURNAL SCIENTIFIC OF MANDALIKA (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2023)
Acid mine drainage (AAT) is water formed at mining sites with a low pH (pH<6) as a result of opening up a potential for rock acidity, causing problems for water quality, rocks containing sulfide minerals. The purpose of this study was to determine the effect of using calcium hydroxide (Ca(OH)2) and aluminum sulphate ((Al2SO4)3) at optimum doses on neutralixing pH and reducing metal content in AAT. This study used a variation of the dose of calcium hydroxide (Ca(OH)2) of 0,5; 0,75; 1; and 1,25 grams and the variation of the dose of aluminum sulphate ((Al2SO4)3) of 1; 1,75; 2,5; and 3,25 grams with a contact time of 20 minutes. The initial concentration of TSS acid mine drainage was 430 mg/L, Fe was 26,92 mg/L, Mn was 7,69 mg/L, and pH was 3,8. The results showed that the doses of calcium hydroxide (Ca(OH)2) and aluminum sulphate ((Al2SO4)3) had an effect on Ph, TSS, Fe, and Mn. TSS removal efficiency was 96,89%, Fe was 99,74%, and Mn was 95,19%.